Patient HIV positive with systemic tuberculosis and osteolytic calvarial lesions mimicking multiple myeloma - Mechán, Victor (2010)
This is the case of a 33 years old man with history of homosexual relations and heavy alcohol drinking. Tobacco, marijuana, cocaine, basic paste and cocaine hydrochloride consumption since age 18. Because of human immunodeficiency virus infection he received irregular treatment (2006-2008) with highly active antiretroviral therapy (HAAT), regulated in the past 12 months. As the patient showed positive resistant acid-fast bacilli he received since June 2008 standard antituberculous treatment [2RHZE/4(HR)2)] (R: rifampicin; H: isoniazid; Z: pirazinamide; E: ethambutol) that was withdrawn 6 months later when the patient showed pulmonary negative acid fast bacilli. In March 2009 he felt intense lumbar pain, difficulty in walking, hypertrophy of cervical lymph nodes, cough and fever. Cervical lymph node discharge culture disclosed M. tuberculosis resistant to rifampicin. Imagenology showed several lytic lesions in skull and thoraco-lumbar vertebrae; also renitent swellings in scalp, right forearm and left rib cage. After multiple myeloma and metastatic cancer were excluded, the patient received multidrug resistant tuberculosis treatment added to HAAT, showing two months later involution of renitent swellings, absence of fever and overall improvement. After 16 months of supervised treatment, the patient gained 7 kg and all symptomatology previously present dissappeared. We discuss the pathophysiology of craniovertebralosteolyticlesions inapatientwithcoinfectionof human immunodeficiency virus and tuberculosis.